Perancangan Sistem Risk Monitoring Dan Data Warehouse Cargo Berbasiskan Web Menggunakan Metode Agile Software Development (Studi Kasus : PT. Bangun Desa Logistik) - Rifky Arisandi Putra; Niki Ratama (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
In the implementation of processing the manifest cargo data storage is still in the form of an archive. Where the data is at risk of being lost or damaged. Existing data is done by being recorded to compile the required reports and also difficulties when looking for manifest cargo data from the previous date so that it takes a long time to find the data. Besides that, in the warehouse there is also no application system to review the level of presentation of damage to goods that occur in the warehouse. In this research, there are several methodologies applied to solve the problem. The research methodologies carried out are Research Places, Data Collection such as literature studies, observations and interviews, System Development Methods. In designing the application risk monitoring system and data warehouse, the methodology used is Agile Software Development Assisting the warehouse in improving the archiving / storage of data that was previously still in hardcopy form and Facilitating the warehouse and cargo party in searching for cargo data on the previous date and Assisting in reviewing risk of damage to goods that occur in the warehouse The conclusion of this application program is to increase productivity so there is still a lot of free time that can be used for other activities and with this application program there is no need for difficulties in monitoring goods and customers and with this application program you can make regular reports and With this application program, it is easier to import data from excel to application programs and this application program can track goods in good condition, damaged, lacking and lost.